A Real Time Node Identity Based Multi Algorithm Framework for Enhancing MANET Performance - Gnanavel, S.; Muruganandam, S.; Balamurugan, G.; Duraimurugan, N. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In Mobile Ad-hoc Network security in data transmission and efficient power utilizations are two major concerns. Maintaining the reliability during the information transference in routing is another major issue, due to the existence of routing threats in the networks. The stability of the networks is reduced. The reliable and energy efficient route is identified to deliver the information packets from origin to target point. This paper proposes a Real Time Node Identity Based Multi Algorithm Framework that enhances the performance of a network. The energy effective cluster head searching algorithm is used to minimize the power utilization of the networks. The selection of cluster header is based on various trust factors of a node; the node trust is measured by various quality attributes of a node such as mobility of a node, energy consumption of a node, degree of connectivity of a node and reliability value of a node. The measurements of all these attributes are estimated for all nodes in the network. The reliability value of a node is estimated by the cumulative value of all these attributes. The reliability value is used for identifying the suspicious nodes in the network. The proposed method RTNIDBMAF introduces four algorithms, the first algorithm supports to measure the energy efficient clusters header node. This efficient cluster header node will determine the optimum path in the network. Second algorithms are used to perform malicious node detection and removal based on the value of vulnerability index. The reliability in data transmission is improved through malicious node detection and removal methods. Third algorithm is used to perform energy optimized routing based on energy consumption of a node. The fourth algorithm is used to perform secure data transmission in routing by applying public key cryptographic methods. The efficiency of the developed algorithm is measured by the simulation results. The proposed algorithms enhance the Quality of Services in Mobile Ad-hoc networks while comparing with existing methods and the results are displayed in the graph.